A comparative study on the indicative function of species and traits structure of stream macroinvertebrates to human disturbances - Wanxiang Jiang (Elsevier, 2021)
The selection of suitable indicators is the key to the development of multi-metric bioassessment. Here, we examined how taxonomic and functional structures of macroinvertebrate communities responded to the environmental gradients in ten mountainous streams in the Weihe River and Hanjiang River basins, two subtropical biodiversity hotspots in central China. Our main objectives were: 1) to examine whether trait-based metrics performed better than taxonomic compositions in differentiating environmental gradients; 2) to test whether indicators (species and traits) were more efficient than entire communities in discriminating three site groups subjected to different levels of human disturbances. Our results showed that both taxonomic and functional trait compositions, including species- and trait-based indicators, were all sensitive to environmental disturbance. Particularly, the trait-based variables responded more sensitive to human disturbances. Indicator assemblages can be effective surrogates of entire communities in response to environmental changes. Traits- and indicators-based metrics should be considered as useful supplements in the existent bio-monitoring schemes in China. We argued that the combination of taxonomic and functional indicators should be implemented in bioassessment, as they reflect different aspects of environmental changes and anthropogenic disturbances.